Economic growth experience of West African region: does human capital matter? (2015)
This paper empirically investigates the relevance of educational and health components of human capital to economic growth, using a panel data from sixteen West African countries over the period 1980 to 2013. GDP per capita is linked to health and education capital while accounting for population growth, physical capital, trade openness, and other growth control variables. To correct for endogeneity and other estimation problems this paper employs Diff-GMM dynamic panel technique. Empirical findings indicate that coefficients of both education and health have positive statistically significant effects on GDP per capita. The paper affirms the strong relevance of human capital to economic growth of West Africa. It is recommended that increased resources and policy initiatives to motivate and enhance access to both health and education by the population should be pursued by policy makers.